VEGF promotes tendon regeneration of aged rats by inhibiting adipogenic differentiation of tendon stem/progenitor cells and promoting vascularization. Issue 8 (22nd July 2022) - Lai, Fan; Wang, Jingjing; Tang, Hong; Huang, Pan; Liu, Juan; He, Gang; Zhou, Mei; Tao, Xu; Tang, Kanglai
Abstract: Studies have shown that the stem cell microenvironment is a key factor for stem cell maintenance or differentiation. In this study, we compared the expression of 23 cytokines such as IL‐6, IL‐10, and TNFα between young and aged rats during patellar tendon repair by cytokine microarray, and found that significant difference between IL‐10, G‐CSF, and VEGF at 3, 7, or 14 days post‐operatively. The effects of these factors on adipogenic differentiation of TPSCs were examined through western blot and oil red O experiments. It was shown that VEGF had an inhibitive effect on the adipogenic differentiation of TPSCs. SPP‐1 was figured out as our target by RNA sequencing and confirmed by western blot in vitro. Further in vivo studies showed that adipocyte accumulation was also decreased in the tendons of aged rats after injection of VEGF and the histological score and biomechanical property were also improved via targeting SPP‐1. Furthermore, histochemical results showed that vascularization of the injury sites was significantly elevated. In conclusion, VEGF not only plays an important role in decreasing adipocyte accumulation but also improves vascularization of the tendon during aged tendon healing. We believe active regulation of VEGF may improve the treatment of age‐related tendon diseases and tendon injuries.